Hyperinfection by Strongyloides stercoralis in a Renal Transplant Patient with SARS-CoV-2 Viral Coinfection - Vicente, Gabriel M.; Rodriguez, María F. (Revista del Hospital Italiano de Buenos Aires, 2026)
A 74-year-old male with a history of kidney transplantation and recent corticosteroid pulse therapy was admitted with fever and abdominal pain, initially attributed to a urinary tract infection. He progressed with hemoptysis, dyspnea, and respiratory failure, and was diagnosed with Strongyloides stercoralis hyperinfection syndrome, confirmed by colonic biopsy and bronchoalveolar lavage, in co-infection with SARS-CoV-2. Treatment with ivermectin and albendazole was initiated, leading to clinical recovery and parasitic eradication. Notably, the patient had a negative stool parasitology prior to transplantation. Strongyloides stercoralis infection is prevalent in tropical and subtropical regions. Diagnosis is challenging due to the low sensitivity of stool tests and limited availability of molecular methods, which may delay treatment.
Keywords: Hyperinfection; Strongyloides stercoralis; COVID-19; Immunosuppression; Kidney transplant